ValidatorDB: database of up-to-date validation results for ligands and non-standard residues from the Protein Data Bank - Sehnal, David; Svobodová Vařeková, Radka; Pravda, Lukáš; Ionescu, Crina-Maria; Geidl, Stanislav; Horský, Vladimír; Jaiswal, Deepti; Wimmerová, Michaela; Koča, Jaroslav (Nucleic acids research, 2015)
Following the discovery of serious errors in the structure of biomacromolecules, structure validation has become a key topic of research, especially for ligands and non-standard residues. ValidatorDB (freely available at http://ncbr.muni.cz/ValidatorDB) offers a new step in this direction, in the form of a database of validation results for all ligands and non-standard residues from the Protein Data Bank (all molecules with seven or more heavy atoms). Model molecules from the wwPDB Chemical Component Dictionary are used as reference during validation. ValidatorDB covers the main aspects of validation of annotation, and additionally introduces several useful validation analyses. The most significant is the classification of chirality errors, allowing the user to distinguish between serious issues and minor inconsistencies. Other such analyses are able to report, for example, completely erroneous ligands, alternate conformations or complete identity with the model molecules. All results are systematically classified into categories, and statistical evaluations are performed. In addition to detailed validation reports for each molecule, ValidatorDB provides summaries of the validation results for the entire PDB, for sets of molecules sharing the same annotation (three-letter code) or the same PDB entry, and for user-defined selections of annotations or PDB entries.
Keywords: konformace proteinů; Molecular Sequence Annotation; Ligands; Reproducibility of Results; Models, Molecular; databáze proteinů; Amino Acids; reprodukovatelnost výsledků; proteiny; Protein Conformation; molekulární modely; aminokyseliny; internet; anotace sekvence; Databases, Protein; Internet; ligandy; Proteins